Relationship between Learning Interest and Cognitive Ability with Learning Outcomes of Al-Qur'an and Hadith at MtsN Binjai - Winda Novianti (Pena Cendekia Insani, 2023)
The purpose of this study was to reveal the relationship between learning interest and cognitive abilities with learning outcomes of the Al-Qur'an and Hadith at MTsN Binjai. The population of this study were all 8th grade students, totaling 163 people. A sample of 62 students was calculated using the Yamane taro formula, namely sampling was carried out using a proportional stratified random sampling technique. The research instrument used a questionnaire and was tested on 30 class VIII students who were not the research sample. The research data were analyzed using correlation and regression to examine the relationship between interest and cognitive abilities with learning outcomes. The results of the data analysis found that: 1) student learning interest has a positive relationship with student learning outcomes where the higher the student learning interest, the higher student learning outcomes. 2) students' cognitive abilities are positively related to student learning outcomes where the higher students' cognitive abilities, the higher their learning outcomes, 3) learning interest and cognitive abilities together have a positive relationship with students' learning outcomes of the Qur'an and Hadith.